1978
DOI: 10.1007/bf00224364
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure and renewal of the intestinal epithelium of the juvenile grasscarp, Ctenopharyngodon idella (Val.)

Abstract: The intestinal absorptive epithelium of starved and fed fish has been studied electron microscopically. After feeding, cells of the proximal segment of the intestine show morphological characteristics of lipid absorption. Absorptive cells in the middle segment contain many pinocytotic vesicles in both fasted and fed specimens. Absorption of protein macromolecules is supposed to be one of the main functions of this part of the gut. In the most caudal part of the intestine, absorptive cells carry relatively few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
59
1
7

Year Published

1979
1979
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 22 publications
11
59
1
7
Order By: Relevance
“…These observations suggest that the enterocytes of the anterior portion of the intestine are involved in lipid absorption. This suggestion is in accordance with that of Stroband and Debets (1978), in Ctenopharyngodon idella, Anderson (1986), in Girella tricuspidata, Deplano et al (1989), in Dicentrarchus labrax, Olsen et al (1999), in Salvelinus alpinus, Gallagher et al (2001), in Lagodon rhomboids, Caballero et al (2003), in Sparus aurata, Kozarić et al (2004), in Merluccius merluccius, and Carrassón et al (2006), in Dentex dentex. Moreover, Fontagné et al (1998), in Cyprinus carpio, stated that the intestinal fat droplets can be interpreted as a temporary storage form of the re-esterified fatty acids.…”
Section: In Esox Lucius and Silurus Glanis Andsupporting
confidence: 78%
See 1 more Smart Citation
“…These observations suggest that the enterocytes of the anterior portion of the intestine are involved in lipid absorption. This suggestion is in accordance with that of Stroband and Debets (1978), in Ctenopharyngodon idella, Anderson (1986), in Girella tricuspidata, Deplano et al (1989), in Dicentrarchus labrax, Olsen et al (1999), in Salvelinus alpinus, Gallagher et al (2001), in Lagodon rhomboids, Caballero et al (2003), in Sparus aurata, Kozarić et al (2004), in Merluccius merluccius, and Carrassón et al (2006), in Dentex dentex. Moreover, Fontagné et al (1998), in Cyprinus carpio, stated that the intestinal fat droplets can be interpreted as a temporary storage form of the re-esterified fatty acids.…”
Section: In Esox Lucius and Silurus Glanis Andsupporting
confidence: 78%
“…NoaillacDepeyre and Gas (1974 and1976), in Cyprinus carpio and Tinca tinca, respectively, and Olsen et al (1999), in Salvelinus alpinus, suggested that the endocytosis of lipid is not a major route of lipid absorption in the anterior intestine enterocytes. Moreover, Stroband and Debets (1978) stated that the anterior and middle segments of the intestine of the herbivorous Ctenopharyngodon idella possess endocytotic vesicles to uptake protein macromolecules.…”
Section: In Esox Lucius and Silurus Glanis Andmentioning
confidence: 99%
“…Segment 2 of the intestine (Fig. 1 A) is involved in absorption of other macromolecules, whereas a short distal domain (segment 3) is postulated to participate in water and ion transport (26,38,39).…”
Section: The Zebrafish Microbiota Affects Epithelial Renewal and Entementioning
confidence: 99%
“…In larval and adult stomachless teleosts, macromolecules taken up from the segment 2 lumen are transported through a network of superficial invaginations and vesicles in enterocytes to large supranuclear vacuoles, where they are stored and͞or degraded (26,38,39). A similar tubulovesicular network exists in neonatal mammalian enterocytes (40)(41)(42) but disappears at the time of initiation of protein digestion.…”
Section: The Zebrafish Microbiota Affects Epithelial Renewal and Entementioning
confidence: 99%
See 1 more Smart Citation